2006
DOI: 10.1002/elan.200503428
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Abasic Site‐Containing DNA

Abstract: A simple and rapid approach for detecting apurinic (AP) sites in DNA, based on direct stripping chronopotentiometric measurements of the adenine and guanine nucleobases at a graphite electrode is described. Tetrahydrofuranyl residues, lacking a nucleobase moiety, were utilized for designing the AP sites and were incorporated in 19-mer oligonucleotides. The change of adenine-to-guanine response ratio (A/G) in one-, two-or three-substituted adenosine residues for stable analogs of AP sites was exploited for elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A simple and rapid approach for detecting apurinic sites in DNA, based on direct stripping chronopotentiometric measurements of Ade and Gua nucleobases at a PeGE was described [ 35 ]. Experiments with mixtures of free nucleobases and purine nucleosides revealed that the larger A/G ratio observed in the electrochemical analysis of apurinic site-containing oligomers is attributed to the influence of the acid and/or thermal decomposition products.…”
Section: Nucleobase Assemblies On Solid Electrodementioning
confidence: 99%
“…A simple and rapid approach for detecting apurinic sites in DNA, based on direct stripping chronopotentiometric measurements of Ade and Gua nucleobases at a PeGE was described [ 35 ]. Experiments with mixtures of free nucleobases and purine nucleosides revealed that the larger A/G ratio observed in the electrochemical analysis of apurinic site-containing oligomers is attributed to the influence of the acid and/or thermal decomposition products.…”
Section: Nucleobase Assemblies On Solid Electrodementioning
confidence: 99%
“…More recently, studies have reported the detection of these damaged sites specifically in synthetic oligonucleotides using chronopotentiometric and square wave voltammetric techniques (32-35). These systems, however, possess intrinsic limitations that prevent them from serving as practical diagnostics.…”
mentioning
confidence: 99%
“…Early work first demonstrated the sensitivity of electrochemical techniques to the presence of abasic sites resulting from depurination in chromosomal DNA: differential poloragraphic responses were observed for nondenatured DNA versus the apurinic form . More recently, studies have reported the detection of these damaged sites specifically in synthetic oligonucleotides using chronopotentiometric and square wave voltammetric techniques . These systems, however, possess intrinsic limitations that prevent them from serving as practical diagnostics.…”
mentioning
confidence: 99%
“…The electrochemical immunosensor that utilizes integrating enzyme assisted signal amplification processes, and incorporates nanomaterials to increase loading of tags has been demonstrated to be one of the most practical solutions due to its capability to conduct highly molecular specific measurements. [25][26][27] Among the nanomaterials used, nanoporous structures have attracted considerable attention due to their promising potential in the use of catalysis, 28 lithium ion batteries, 29 photodynamic therapy 30 and electrical conduction. 31 Owing to their bicontinuous nanoscale skeletons and interconnected hollow channels, they are favorable for easy mass transport and high electron conductivity.…”
Section: Introductionmentioning
confidence: 99%